KAJIAN MISKONSEPSI MAHASISWA PENDIDIKAN BIOLOGI FPMIPA IKIP MATARAM TENTANG EVOLUSI - Laras Firdaus; Taufik Samsuri (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2018)
The purpose of this study is to identify and explain the evolutionary concept errors of FPMIPA IKIP Mataram students. Knowing misconceptions or misconcepts is a starting point for designing better learning to eliminate these misconceptions. This research is a descriptive survey research. Respondents in this study were 50 students majoring in biology FPMIPA IKIP Mataram who had taken the evolution course. Data were obtained using a questionnaire consisting of 10 statements, and then measures of the level of students' misconceptions about evolution were analyzed using a certainty of response index (CRI). Based on the results of this study it was concluded that students experience misconceptions about evolution, or have a low understanding of evolution, so it is also suggested to supplement the literature sources or learning resources for students, which in this case are books or handouts that are suitable (free of misconceptions), with the hope students will have a better understanding of evolution.